2014
DOI: 10.1371/journal.pone.0088858
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual Anal Sex among Female Sex Workers in High HIV Prevalence States of India: Need for Comprehensive Intervention

Abstract: IntroductionRole of vaginal sex in heterosexual transmission of HIV has been investigated but that of heterosexual anal sex (HAS) is not fully understood. This paper examines practice of HAS among Female Sex Workers (FSWs) and its correlates in India where the HIV epidemic is being primarily driven by core groups like FSWs.MethodsData for this paper are drawn from Round I survey of 9667 FSWs in the Integrated Biological and Behavioral Assessment (IBBA) from 23 districts of 4 high HIV prevalent states of India.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
3
21
1
Order By: Relevance
“…106 Interestingly, heterosexual anal sex was reported by 11.9% of FSW in four high prevalence states in India. 107 Meta-analysis of studies from developed countries has shown that the probability of HIV transmission is higher per act of receptive anal sex (1.7%) as compared to penovaginal sex (0.8%). 79 vaccine clinical development have been deployed in the region since the mid-1990s.…”
Section: Indiamentioning
confidence: 99%
“…106 Interestingly, heterosexual anal sex was reported by 11.9% of FSW in four high prevalence states in India. 107 Meta-analysis of studies from developed countries has shown that the probability of HIV transmission is higher per act of receptive anal sex (1.7%) as compared to penovaginal sex (0.8%). 79 vaccine clinical development have been deployed in the region since the mid-1990s.…”
Section: Indiamentioning
confidence: 99%
“…Five VOICE-D participants also reported that condoms were not used when they experienced forced PAI. Evidence from other studies suggests that women who sell sex are also more likely to experience coerced condom non-use for PAI, and frequent condom breakage [23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the anal HPV prevalence noted in our study was much lower than that reported from other countries. The sparse Indian data on heterosexual anal sex are available primarily from female sex workers with rates ranging from 11.9% in a multicentric study across 4 Indian states 18 to 27% in Andhra Pradesh and Karnataka. 2,11 The prevalence of concomitant cervical and anal HPV infections in our study was a little over 5% and could suggest the potential utility of screening HIV-infected women with cervical HPV or cervical cytological abnormalities for anal HPV infection.…”
Section: Discussionmentioning
confidence: 99%